The Growth of PB 260 Clone of Rubber Plant on Peatland - Jamin Saputra; Alchemi Putri Juliantika Kusdiana (Program Pascasarjana Universitas Sriwijaya, 2023)
The expansion of the area for the cultivation of rubber plants is hampered by the fact that the availability of mineral land has begun to decrease, so many have started to plant rubber on marginal lands such as peatlands. Peatlands for agriculture have many limiting factors, but if peatlands are adequately managed with drainage as well as ameliorant and fertilizing inputs, then peatlands have the potential to be used as agricultural land. However, information on research results related to rubber cultivation on peatlands is still very limited, so this study was carried out to observe the growth of rubber plants of PB 260 clones on peatlands. The research was carried out for five years in Sungai Rengit Village, South Sumatra, using rubber planting material in a polybag of PB 260 clones. The observations' parameters were stem girth, peat water level, and peat subsidence. The results showed that the growth of PB 260 clones during the immature plant period on peatland was not significantly different from rubber plants on mineral soils. At the research location, there was never any puddle and the peat water level was maintained because the drainage channels were well made. During the five years of observation, the highest peat water level occurred in the rainy season at 27 cm from the peat surface, while the lowest peat water level occurred in the dry season, which was more than 150 cm from the peat surface. The peat decline reached 25 cm during the five years of observation